A successfully treated Basal Cell Carcinoma using elliptical excision surgery - Irmadita Citrashanty; Hamidah Luthfidyaningrum; Evy Ervianti; Bagus Haryo Kusumaputra; Maylita Sari; Muhammad Yulianto Listiawan; Yoana Fransiska Wahyuning Christi (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2023)
Â Basal cell carcinoma (BCC) is a non-keratinization cell-derived neoplasm. Surgical excision is the most common way to remove a tumor. The excision depends on the tumor type, size, and location. This paper reported a 44- years-old woman presented with the chief complaint of a single bump that bleeds easily in the facial region that began one year ago. Dermatology examination revealed hyperpigmented plaque with an ulcer in central, solitary, oval, 2 cm x 1 cm in size, covered with blackish crust on top. A Dermoscopy examination showed blue dots and globules, arborizing vessels, and ulceration. Histopathology examination findings were in concordance with BCC. The patient was treated with elliptical surgical excision. The lesion was successfully removed and showed good results with minimal scarring. BCC occurs in 75% of all skin cancers. Elliptical surgical excision on the left cheek was performed after considering the location anatomy, defect size, age, and general condition patient and postoperative cosmetic estimates. The minimal scar that occurs is planned to be performed with a fractional laser. The prognosis is generally good. There is no recurrence until one year later. In conclusion, elliptical surgical excision is an effective standard treatment if performed with a safe margin. In this case, we used 5 mm safe outer margin.